The role of chemical and microstructural inhomogeneities on interface magnetism. (22nd February 2021) - Laureti, S; Gerardino, A; D'Acapito, F; Peddis, D; Varvaro, G
Abstract: The study of interfacing effects arising when different magnetic phases are in close contact has led to the discovery of novel physical properties and the development of innovative technological applications of nanostructured magnetic materials. Chemical and microstructural inhomogeneities at the interfacial region, driven by interdiffusion processes, chemical reactions and interface roughness may significantly affect the final properties of a material and, if suitably controlled, may represent an additional tool to finely tune the overall physical properties. The activity at the Nanostructured Magnetic Materials Laboratory (nM 2 -Lab) at CNR-ISM of Italy is aimed at designing and investigating nanoscale-engineered magnetic materials, where the overall magnetic properties are dominated by the interface exchange coupling. In this review, some examples of recent studies where the chemical and microstructural properties are critical in determining the overall magnetic properties in core/shell nanoparticles, nanocomposites and multilayer heterostructures are presented.